A new important species of Nymphidae (Neuroptera) from the Lower Cretaceous Crato Formation of Brazil - Makarkin, Vladimir N. (Zootaxa, 2022)
Olindanymphes? headsi sp. nov. (Neuroptera: Nymphidae) is described from the late Aptian (Lower Cretaceous) Crato Formation of Brazil. Its hindwing is unique in the family by the presence of the few-pectinate both CuA and CuP, each with two to three branches. The few-pectinate CuA in the hindwing is a derived condition known only in three Early Cretaceous species, including the new species.